Perceptual objective evaluation for multimodal medical image fusion - Tian, Chuangeng; Zhang, Juyuan; Tang, Lu (Frontiers in Physics, 2025)
Multimodal medical Image fusion (MMIF) has received widespread attention due to its promising application in clinical diagnostics and treatment. Due to the inherent limitations of fusion algorithms, the quality of obtained medical fused images (MFI) varies significantly. An objective evaluation of MMIF can quantify the visual quality differences in fused images and facilitate the rapid development of advanced MMIF techniques, thereby enhancing fused image quality. However, rare research has been dedicated to the MMIF objective evaluation. In this study, we present a multi-scale aware attention network for MMIF quality evaluation. Specifically, we employ a Multi-scale Transform structure that simultaneously processes these multi-scale images using an ImageNet pre-trained ResNet34. Subsequently, we incorporate an online class activation mapping mechanism to focus visual attention on the lesion region, enhancing representative discrepancy features closely associated with MFI quality. Finally, we aggregate these enhanced features and map them to the quality difference. Due to the lack of dataset for the objective evaluation task, we collect 129 pairs of source images from public datasets, namely, the Whole Brain Atlas, and construct a MMIF quality database containing 1,290 medical fused images generated using MMIF algorithms. Each fused image was annotated with a subjective quality score by experienced radiologists. Experimental results demonstrate that our method produces a satisfactory consistent with subjective perception, superior to the state-of-the-art quality evaluation methods. The source images dataset is publicly available at: http://www.med.harvard.edu/AANLIB/home.html.